Analisis kemampuan numerasi ditinjau dari gaya kognitif pada materi operasi penjumlahan dan pengurangan bilangan pecahan peserta didik kelas v sekolah dasar - Nurfahmi, Rizali; Kurniawan, Sandra Bayu (Didaktika Dwija Indria, 2025)
Abstract. This research conducted to analyzed numeracy skills reviewed from cognitive styles in the addition and subtraction operations of fractional numbers for fifth grade students. This is a qualitative research using a case study approach. The results of this study are as follows. Learners with Field Independent (FI) cognitive style can fulfill all indicators of numeracy skills, although one subject did not fulfill one indicator. On the other hand, students with Field Dependent (FD) cognitive style did not fulfill all indicators of numeracy skills. In general, they still find it difficult to understand the material of the operations of addition and subtraction of fractions correctly, although ???2 and ???3 can write what is known in the problem using their own language or incomplete. The implication of this research states that the creativity of teachers in the learning process to connect one concept of numeracy with another concept and bring the material to the appropriate application form can be an exercise for students to practice numeracy skills. Teachers also need to facilitate students according to their cognitive style so that students numeracy skills can develop optimally.